Development of Augmented Reality Teaching Materials ‎Integrating Local Wisdom to Improve Junior High School ‎Students’ Cultural Literacy - Ike Betria; Ilham Rahmawati; Mirajul Rifqi; Ridwan Sinurat; Okvita Isnawati; Siti Saroha (Yayasan Darussalam Bengkulu, 2026)
Limited access to interactive and context-sensitive learning resources constrains junior high school students’ engagement with local culture. This study developed and evaluated augmented reality (AR)-enhanced digital teaching materials integrating Rokan Hulu Malay local wisdom to support students’ cultural literacy. The study followed the ADDIE model and involved three expert validators, a small-group trial (n = 10), and a large-group trial (n = 30) at SMP Negeri 1 Rambah, Indonesia. The large-group participants completed four 90-minute instructional sessions over two weeks and undertook cultural literacy pretests and posttests. Data were collected through validation sheets, student response questionnaires, and cultural literacy tests. Product validity was examined using Aiken’s V, practicality through descriptive statistics, and score improvement through the Shapiro–Wilk test, a paired-samples t-test, and normalized gain analysis. The materials obtained a mean Aiken’s V of 0.75. Practicality scores were 82.50% in the small-group trial and 82.03% in the large-group trial. Mean cultural literacy scores increased from 61.27 ± 8.15 to 83.43 ± 7.28, t(29) = −13.542, p < .001, with a moderate N-gain of 0.57. The findings indicate that the materials were valid and practical and were associated with improved cultural literacy; however, the one-group design limits causal interpretation.